Potensi Limbah Pertanian sebagai Pupuk Organik Lokal di Lahan Kering Dataran Rendah Iklim Basah - Nurhayati Nurhayati; Ali Jamil; Rizqi Sari Anggraini (Iptek Tanaman Pangan, 2011)
Farm land in Indonesia, both dry land and wet land, generally have low soil organic content, of less than 2%. Therefore, adding organic matter to the soil in order to improve soil productivity is recommended. Crop residues and animal waste are potential as source for organic matter. Composted organic matter can be used as fertilizers containing macro and micro nutrients. The availability of organic fertilizer can be utilzed as a basis to promote sustainable agriculture development. In each district in Indonesia, such as one of Kampar District in Riau Province, the material for organic fertlizer is readily available. It was estimated the crop residues from food crops alone amounted to 40,930 ton per year, crop residues from estate crops amounted to 74,840 ton per year, and animal waste 17,612 ton per year. From those organic matter, when fermented into compost, can be used as fertlizer to cover farm land area of 56,455 ha annually, thus, can be expected to improve soil quality gradually.